2003
DOI: 10.1136/bmj.326.7394.841
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anticholinergic drugs compared with placebo in the treatment of overactive bladder: systematic review

Abstract: Objective To determine the effectiveness of anticholinergic drugs for the treatment of overactive bladder syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
16

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(179 citation statements)
references
References 16 publications
4
159
0
16
Order By: Relevance
“…A power calculation was based on the systematic review by Herbison, which showed that the mean Cmax in people with OAB is 360 ml with a standard deviation of 103; a crossover study with 23 people has a power to detect a di¡erence of 28% in Cmax. [Herbison et al, 2003].…”
Section: Methodsmentioning
confidence: 99%
“…A power calculation was based on the systematic review by Herbison, which showed that the mean Cmax in people with OAB is 360 ml with a standard deviation of 103; a crossover study with 23 people has a power to detect a di¡erence of 28% in Cmax. [Herbison et al, 2003].…”
Section: Methodsmentioning
confidence: 99%
“…Wirkung ist jedoch erheblich und liegt bei mindestens 25% (Herbison et al, 2003;Yarker et al, 1995). Aber auch Medikamente anderer Stoffgruppen zeigten gewisse Therapieerfolge, so z.B.…”
Section: Abbruchrate Dieser Medikamente Aufgrund Von Nebenwirkungen Ounclassified
“…[16][17][18][19] We theorized that IC/BPS may have an association with low back pain; and for a number of patients, the condition may subside when their low back condition improves. It is unknown if there is a casual relationship, but the potential impact of IC/BPS on patients' lives suggests that we consider a potential relationship.…”
Section: Introductionmentioning
confidence: 99%